Levothyroxine liquid solution versus tablet form for replacement treatment in pregnant women. (2nd April 2016) - Cappelli, Carlo; Negro, Roberto; Pirola, Ilenia; Gandossi, Elena; Agosti, Barbara; Castellano, Maurizio
Abstract: Objective: To evaluate the need and the magnitude of levothyroxine (LT4) increase in hypothyroid pregnant women on liquid compared to tablet formulations. Methods : Patients were recruited by searching our "thyroid patients" database. The selection criteria were as follows: a) pregnant women on treatment for hypothyroidism (both liquid and tablet LT4) who gave birth at our hospital between February 2012 and January 2014; b) thyroid stimulating hormone (TSH) and free thyroxine (FT4) levels obtained at least 3 months before missed menstrual cycle, with a TSH value less than 2.5 mIU/L and c) TSH and FT4 obtained within 12 weeks of pregnancy, and each month subsequently. Results : During pregnancy, 8/31 (25.5%) of the women had to increase the dosage of LT4. Of these, 7/17 (41.2%) were on LT4 replacement therapy with tablets, and 1/14 (7.1%) with liquid formulation ( p  = 0.038). Daily LT4 was significantly increased in the liquid group only (52.9 ± 19.5 versus 67.5 ± 19.2 mcg/day ( p  = 0.013). A logistic regression analysis showed that the treatment with LT4 tablets was the only predictor of LT4 increase (OR: 0.44; 95% CI: 0.04–0.83; p  = 0.031). Conclusion: Pregnant women on optimal replacement therapy before pregnancy require an increase of LT4 dosage more often when on a tablet than liquid formulation.